Rising prevalence of venous thromboembolism in gastrointestinal cancers: a nationwide analysis of 205 million hospitalizations, 2016–2022 - Atodaria, Kuldeepsinh Pradipkumar; Patel, Arpeet; Kottapalli, Niharika; Tetali, Pratap; Iqbal, Sabah; Dhruv, Samyak; Parvataneni, Tarun; Cohen, Steven J.; Ashfaq, Ammar (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Venous thromboembolism (VTE), encompassing deep vein thrombosis (DVT) and pulmonary embolism (PE), is a well-recognized complication of malignancy, yet comprehensive data on VTE prevalence across all gastrointestinal cancer (GIC) subtypes are lacking. Using the National Inpatient Sample (NIS) database from 2016 to 2022, we performed a cross-sectional analysis of 205,075,197 adult hospitalizations to quantify the prevalence and temporal trends of DVT, PE and VTE in GIC hospitalizations, and calculated the relative risk (RR) of VTE and inpatient death (IPD) in GICs compared with all hospitalizations. GICs included malignant neoplasms of the esophagus, stomach, small intestine, colon, rectosigmoid junction, rectum, anus and anal canal, liver, intrahepatic bile duct, gallbladder, biliary tract, pancreas, and neuroendocrine tumors. Of 3,663,570 GIC hospitalizations (1.78%), VTE was present in 197,355(5.39%), compared with 2.21% in all hospitalizations (RR =2.44; 95% confidence interval (CI): 2.43–2.45). Pancreatic cancer had the highest VTE prevalence (8.44%), followed by gallbladder (7.05%) and stomach cancer (6.79%). A statistically significant rising trend in VTE prevalence was observed for GICs (Cochran-Armitage P